Kinerja Mekanistik Campuran Beraspal dengan Mensubstitusi Agregat Kasar dengan Batu Vulkanik Merah - Agus Ariawan; D.M. Priyantha Wedagama; I Nyoman Arya Thanaya; I Gusti Agung Ratih Kusuma Wardani; I Putu Chandra Wibawa (Institut Teknologi Bandung, 2023)
Abstract The increasingly limited availability of volcanic stone in nature has caused road pavement construction materials to use black volcanic stone mixed with red volcanic stone, which is lighter in density and porous. This research aims to analyze the mechanistic performance of asphalt mixtures by substituting coarse aggregate with red volcanic stone up to a percentage of 10% at a granule size of ½